The lock-eater - Clark, Zack Loran (Dial Books for Young Readers, 2022)
Melanie Gate, a foundling with a peculiar talent for opening the unopenable, agrees to accompany a gearling automaton named Traveler on his quest to find a home, only to be pursued by the most dangerous wizard in the land and, along the way, discover her true powers.